Clozapine Use Presenting with Pseudopheochromocytoma in a Schizophrenic Patient: A Case Report. (14th January 2013) - Sara, Jaskanwal; Jenkins, Matt; Chohan, Tanveer; Jolly, Karan; Shepherd, Lisa; Gandhi, Nirav Y.; Shakher, Jayadave
Abstract : Introduction . There have been six previous cases that reported pseudopheochromocytoma in patients taking clozapine. Our case showed the direct link of clozapine to serum levels of certain markers. Case . This is a case of a 49-year-old obese Caucasian female who was referred to endocrinology for investigation of Cushing's syndrome, based on raised blood pressure and Cushingoid facies. The patient had underlying schizophrenia and was stable on clozapine. Her blood pressure was 150/99 mmHg on bendroflumethiazide and candesartan. We measured her 24-hour urinary-free cortisol, which was normal but 24-hour urinary-free noradrenaline was elevated at 835 nmol (76–561) with normal adrenaline 36 nmol (7–82) and dopamine 2679 nmol (366–2879), as the patient had history of palpitations and sweating. Two sets of 24-hour urinary-free cortisol measurements were normal and serum cortisol suppressed to <50 nmol/l after a 1 mg overnight dexamethasone. Two further 24-hour urinary-free catecholamines showed a raised level of noradrenaline. MRI demonstrated normal adrenals and MIBG scan did not show any abnormal uptake at adrenal glands. Conclusion . Pseudopheochromocytoma has been reported in patients taking clozapine. A number of different mechanisms for raised plasma noradrenaline levels with clozapine have been postulated. The above case highlights an unusual but known side effect of clozapine.